The Need In Training And Retraining For TVET Teachers In Malaysia - Mohamad, Mimi Mohaffyza; Saud, Muhammad Sukri; Ahmad, Adnan (Journal of Technical Education and Training, 2009)
Malaysia is a fast developing country and to support the growth of Malaysia industrial sector Malaysia needs highly skilled workforce. To fulfill this needs Malaysia has developed many vocational and technical training institutes. Currently there are approximately 194 technical-vocational institutions and there is a plan to increase this number during five next year plan. They are 90 technical schools which provide the vocational course in secondary school level. The Technical and Vocational Education (TVE) in Malaysia started with the enforcement of Razak Report 1956 and Education Ordinance 1957. Other education reports and education memorandum such as Rahman Talib Report and Education Act 1961, Mahathir Report 1979, Cabinet Memorandum 1995, 1998 and 1999 had further sustained the policies, system, curriculum and direction of technical and vocational education. Although the theoretical debate continues, it has been generally that curriculum should be seen as an overall plan for instruction. It consists of a statement of aims and objectives of content in terms of theoretical knowledge, practical skills to be required, attitude towards work and necessary support materials to be used in its presentation. Improving curriculum content has long been regarded as a core-component of TVET. To produce the good quality of TVET in the school level the focus is the teachers those who specialized in their field. Many of teaching staff who were employed possessed necessary technical skills but no had more opportunity to undertake professional training. TVE in Malaysia, there is a shortage of qualified technical and vocational teachers. Most teachers are recruited directly after they graduated from universities and collages based on their academic qualifications and do not have industrial work experience. At the same time qualified personnel with work experience are not willing to become teachers due to the unattractive salary scheme. This paper is a review of the structure and performance of the TVE teachers in Malaysia. It is consists in development of curriculum, program design, the nature of learning materials and stakeholders involvement. Teacher training in TVE can be defined is the main role in providing the skill to fulfill the school level TVE needs. Retraining is defined as upgrading of existing skill or acquiring a new one. Upgrading skills can be by accelerating – by doing and joining program in other TVET institution or center. The performance of teacher in TVE is important to make the Technical School in Malaysia is the selected school for parents to send their children and choose the TVE field as a carrier path. This paper is a discussion the issues in training and retraining needs, strategies introduced to overcome the teaching staff as well as curriculum relevancy. Improving the quality of teachers in TVET is related to raising the quality of technical and vocational education.